Polaron Delocalization in Donor–Acceptor Polymers and its Impact on Organic Electrochemical Transistor Performance - Moser,M; Savva,A; Thorley,K; Paulsen,BD; Hidalgo,TC; Ohayon,D; Chen,H; Giovannitti,A; Marks,A; Gasparini,N; Wadsworth,A; Rivnay,J; et al. (Angewandte Chemie, 2021)
Abstract Donor–acceptor (DA) polymers are promising materials for organic electrochemical transistors (OECTs), as they minimize detrimental faradaic sidereactions during OECT operation, yet their steadystate OECT performance still lags far behind their alldonor counterparts. We report three DA polymers based on the diketopyrrolopyrrole unit that afford OECT performances similar to those of alldonor polymers, hence representing a significant improvement to the previously developed DA copolymers. In addition to improved OECT performance, DFT simulations of the polymers and their respective hole polarons also reveal a positive correlation between hole polaron delocalization and steadystate OECT performance, providing new insights into the design of OECT materials. Importantly, we demonstrate how polaron delocalization can be tuned directly at the molecular level by selection of the building blocks comprising the polymers’ conjugated backbone, thus paving the way for the development of even higher performing OECT polymers.